2015
DOI: 10.1038/pr.2015.156
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and posttranscriptional mechanisms contribute to the dysregulation of elastogenesis in Schimke immuno-osseous dysplasia

Abstract: BACKGROUND: Schimke immuno-osseous dysplasia (SIOD)is an autosomal recessive disorder caused by mutations in SMARCAL1. A frequent complication is arteriosclerosis associated with reduced elastin expression; however, the mechanism underlying the reduced elastin expression remains unknown. METHODS: Expression of transcriptional regulators of elastin (ELN) and microRNA (miRNA) regulators of ELN messenger RNA (mRNA), ELN promoter methylation, and ELN mRNA poly(A) tail length were assessed by quantitative RT-PCR, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…Most importantly, loss of SMARCAL1 affects expression of a subset of germ layer-specific master genes, which can be rescued through inhibition of DDR signalling. The pathogenetic mechanisms responsible for SIOD are still elusive; however, SMARCAL1 deficiency has been reported to pathologically modulate gene expression (Baradaran-Heravi et al, 2012; Morimoto et al, 2015, 2016a,b; Sanyal et al, 2015). An intriguing possibility is that loss of SMARCAL1 function indirectly influences gene expression through increased levels of replication stress, as has been suggested for loss of WRN or FANCJ helicase (BRIP1) (Khurana and Oberdoerffer, 2015; Papadopoulou et al, 2015; Schiavone et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, loss of SMARCAL1 affects expression of a subset of germ layer-specific master genes, which can be rescued through inhibition of DDR signalling. The pathogenetic mechanisms responsible for SIOD are still elusive; however, SMARCAL1 deficiency has been reported to pathologically modulate gene expression (Baradaran-Heravi et al, 2012; Morimoto et al, 2015, 2016a,b; Sanyal et al, 2015). An intriguing possibility is that loss of SMARCAL1 function indirectly influences gene expression through increased levels of replication stress, as has been suggested for loss of WRN or FANCJ helicase (BRIP1) (Khurana and Oberdoerffer, 2015; Papadopoulou et al, 2015; Schiavone et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It has long been hypothesized that SMARCAL1 might be transcriptionally regulating a subset of genes, and failure of this process results in pathophysiological features associated with various diseases. 8,[55][56][57] Baradaran-Heravi postulated that SMARCAL1 with its ability to recognize specific DNA structure would be able to regulate the expression of genes such as c-kit because of the presence of specific structures in their promoters. 58 The first evidence that the hypothesis might be true came from studies where SMARCAL1 was shown to negatively regulate the expression of c-MYC 7 (Figure 3).…”
Section: Smarcal1 Is a Transcriptional Co-regulatormentioning
confidence: 99%
“…Schimke immuno-osseous dysplasia (SIOD) is an uncommon AR disorder due to mutations in the SMARCAL1 gene, which encodes for chromatin-remodeling enzyme necessary for stabilizing stalled replication forks, restricting DNA damage due to its replication [ 1 ]. The vascular changes in this disorder are due to disorganized elastogenesis with reduced elastin expression within the vessel, resulting in the defective internal elastic lamina and hyperplasia of intima or media [ 3 ]. This disorder manifests as spondylo-epiphyseal dysplasia (SED), immunodeficiency, growth retardation, and nephropathy.…”
Section: Discussionmentioning
confidence: 99%